2019
DOI: 10.1016/j.redox.2019.101197
|View full text |Cite
|
Sign up to set email alerts
|

Ku80 promotes melanoma growth and regulates antitumor effect of melatonin by targeting HIF1-α dependent PDK-1 signaling pathway

Abstract: Melanoma is one of the most malignant and aggressive cancers with high cancer-related deaths. However, it is unclear whether Ku80 regulates tumor growth in human melanoma. In this study, we screened a siRNA library targeting 6024 human genes and identified Ku80 as a potential therapeutic target in melanoma cells. Knockdown of Ku80 significantly suppressed melanoma cell proliferation and induced apoptosis, as well as enhanced the antitumor effect of melatonin in melanoma in vitro and in vivo. Overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In infertile male testes, melatonin has anti-proliferative, anti-inflammatory and antioxidant effects on local macrophage and mast cell populations [11]. Moreover, melatonin has a pro-apoptotic effect on tumor cells, indicating that melatonin has an anti-tumor effect [12]. In addition, melatonin may increase androgen production in co-cultured Leydig and Sertoli cells by regulating the expression of insulin-like growth factor 1 regulated by melatonin receptor 1 and the inhibition of estrogen synthesis induced by melatonin receptor 1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In infertile male testes, melatonin has anti-proliferative, anti-inflammatory and antioxidant effects on local macrophage and mast cell populations [11]. Moreover, melatonin has a pro-apoptotic effect on tumor cells, indicating that melatonin has an anti-tumor effect [12]. In addition, melatonin may increase androgen production in co-cultured Leydig and Sertoli cells by regulating the expression of insulin-like growth factor 1 regulated by melatonin receptor 1 and the inhibition of estrogen synthesis induced by melatonin receptor 1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, melatonin significantly inhibits HIF-1α induction [ 45 ], being another route, along with antagonism of the AhR and TGF-β, whereby the suppression of melatonin will contribute to immune suppression driven by adenosine A2Ar activation. Hypoxia/HIF1-α alters OXPHOS and mitochondrial metabolism in tumours by inducing Ku80, which binds and activates the pyruvate dehydrogenase kinase (PDK)1 promoter, thereby acting to inhibit the pyruvate dehydrogenase complex (PDC), in turn inhibiting the PDC conversion of pyruvate to acetyl-CoA, which is crucial to driving OXPHOS, the TCA cycle and the melatonergic pathway [ 46 ]. See Figure 1 .…”
Section: Tumour Microenvironment and Immune Suppression: Exhaustiomentioning
confidence: 99%
“…See Figure 1 . Melatonin degrades and inhibits HIF1-α in tumours, thereby increasing apoptosis [ 46 ], again indicating the impact that variations in local melatonin production can have on core tumour regulators [ 47 ]. Taking pyruvate away from acetyl-CoA production and driving it to lactate production is an important mediator of key changes in tumour metabolism, as indicated by acetate supplementation leading to tumour cell differentiation under hypoxia [ 48 ].…”
Section: Tumour Microenvironment and Immune Suppression: Exhaustiomentioning
confidence: 99%
“…Melatonin (N‐acetyl‐5‐methoxytryptamine) is an indoleamine compound, most of which is synthesized and secreted by the pineal gland. It is well known that melatonin is involved in the regulation of circadian rhythms and endocrine functions 19 . Actually, melatonin has been reported to participate in many other functions, including antioxidation, anti‐angiogenesis, anti‐inflammatory and activation of the immune system 20‐23 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that melatonin is involved in the regulation of circadian rhythms and endocrine functions. 19 Actually, melatonin has been reported to participate in many other functions, including antioxidation, anti-angiogenesis, anti-inflammatory and activation of the immune system. [20][21][22][23] In recent years, increasing evidence has demonstrated that melatonin has anti-tumour effect in various cancers, such as melanoma, breast cancer, lung carcinoma and thyroid cancer.…”
mentioning
confidence: 99%